Take-Off Time of the First Generation of the Overwintering Small Brown Planthopper, Laodelphax striatellus in the Temperate Zone in East Asia - Sanada-Morimura, Sachiyo (PLoS One, 2015)
Overseas migration of the small brown planthopper, Laodelphax striatellus (Fallén), occurs during the winter wheat harvest season in East Asia. Knowing the take-off time of emigrating L. striatellus is crucial for predicting such migrations with a simulation technique because winds, carriers of migratory insects, change continuously. Several methods were used in China and Japan from late May to early June 2012 and again in 2013 to identify the precise timing of take-off. These methods included: a tow net trap mounted to a pole at 10 m above the ground, a helicopter-towed net trap, and a canopy trap (which also had video monitoring) set over wheat plants. Laodelphax striatellus emigrated from wheat fields mainly in the early evening, before dusk. The insects also emigrated during the daytime but rarely emigrated at dawn, showing a pattern that is unlike the bimodal emigration at dusk and dawn of two other rice planthoppers, the brown planthopper, Nilaparvata lugens (Stål), and the white-backed planthopper, Sogatella furcifera (Horváth). There was no significant difference in the temporal pattern of take-off behavior between females and males of Japanese L. striatellus populations.